c.1 - Indian Law Institute (Bombay, 1980)
The book vividly mentions the various legal problems confronting today because of serious environ mental pollution of water, air and noise. The acuteness of the problem and its deteriorating impact on human health has been sufficiently projected. The different elsant statutory provisions in this context have been analysed and evaluated. It contains useful suggestions for the improvement in the Water (Prevention and Control of Pollution) Act, 1974 and for the enactment of suitable comprehensive central legislation on air and noise pollution. Proposals are also incorporated in this book to introduce Environmental Pollution' as a subject of study in the law schools curricula.
Keywords: Environmental law -India.